Cemetery girl - Bell, David, 1969 November 17- (NAL Trade, 2011)
"Tom and Abby Stuart had everything: a perfect marriage, successful careers, and a beautiful twelve-year-old daughter, Caitlin. Then one day Caitlin vanished without a trace. For a while they grasped at every false hope and followed every empty lead, but the tragedy ended up changing their lives, overwhelming them with guilt and dread, and shattering their marriage. Four years later, Caitlin is found alive--dirty and disheveled yet preternaturally calm. She won't discuss where she was or what happened. Then the police arrest a suspect connected to the disappearance, but Caitlin refuses to testify, leaving the Stuarts with a choice: Let the man who may be responsible for destroying their lives walk away, or take matters into their own hands. And when Tom decides to try to uncover the truth for himself, he finds that nothing that has happened yet can prepare him for what he is about to discover"--